Computational investigation on the surface cutting of γ-TiAl alloy. (1st February 2022) - Jiang, Junqiang; Dong, Zhaowei; Ma, Hongwei; Sun, Lihui
Abstract: Due to outstanding mechanical and physical properties, γ-TiAl has been widely used in aeroengine through metal cut into various well-designed parts. To deliver high-quality products, cutting parameters need to extensively be optimized. In this work, molecular dynamics simulation has been used to investigate the relationship between operating parameters (cutting speed and depth) and surface structures at the atomic scale. It is found that material removal of γ-TiAl alloy workpiece is dominated by the extrusion and shearing between cutting tool and workpiece. Associated with the processing retreat, surface atoms present an upward elasticity recovery, indicating that elastic deformation and ploughing are introduced. Especially, large cutting depth and cutting speed will lead to severe local force as revealed by strain analysis. As a result, remarkable temperature increase has been resulted in within the cutting region. After removing constraints and full relaxation, cutting-associated strains are partially released, leaving improved compressible local surfaces with higher mechanical quality. Highlights: Using the cutting of γ-TiAl Alloy with nonrigid diamond tool based on MD. Both shear and extrusion mechanisms are presented during the cutting. The chip deformation is mainly affected by cutting depth, rather than cutting speed. The friction coefficient decreases when higher speed applies. Large cutting depth can improve the mechanical properties of machined surface.